2012
DOI: 10.1007/s00428-012-1209-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of KRT7 and WT1 differentiates precursor lesions of Wilms’ tumours from those of papillary renal cell tumours and mucinous tubular and spindle cell carcinomas

Abstract: Wilms' tumours (WT) and adult papillary renal cell tumours (pRCT) are associated with precursor lesions of embryonic origin. The aim of this study was to analyse the expression of WT1, KRT7, KRT8, KRT18 and KRT19 genes by immunohistochemistry in 74 precursor lesions associated with WTs, pRCTs and mucinous tubular and spindle cell carcinomas (MTSCC). All precursor lesions associated with Wilms' tumours were positive for WT1, whereas all precursor lesions in pRCT and MTSCC-bearing kidneys were negative. None of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Of interest, MET is also expressed in 22% of nephrogenic rest and 14% of WTs mainly in well-differentiated epithelial cells, whereas blastemal components are negative in both nephrogenic rests and WTs 19 . In spite of this similarity, the precursor lesions for WT and PRCT correspond to distinct stages of cellular differentiation 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, MET is also expressed in 22% of nephrogenic rest and 14% of WTs mainly in well-differentiated epithelial cells, whereas blastemal components are negative in both nephrogenic rests and WTs 19 . In spite of this similarity, the precursor lesions for WT and PRCT correspond to distinct stages of cellular differentiation 20 .…”
Section: Resultsmentioning
confidence: 99%
“…29 additional events involved truncation, occurring in non-NMD genes and included five of the 29 PD signature genes that we previously identified in this same cohort: the B cell development controller LRRC8C, the solute carrier protein SLC6A8, the ATPase ATP11B, the cell division cycle protein CDC20 and TKTL1 [35]. Two genes showed both fold-change and modified AS: the tumorigenic keratin KRT7 [44] and the oncogene MED29 [44]. Functional analysis revealed that the FIRMA-detected genes were highly enriched with alternative splicing.…”
Section: Resultsmentioning
confidence: 99%
“…The similarity of morphological variations in precursor lesions and clinically recognised MTSCC strongly suggest that MTSCC develops from such lesions. In 1882 Cohnheim has postulated 1, -4, -6, -9, -13, -14, -15, -18, -22 -1, -6, -8, -11, -14, -15, -22 1 -1,-3,-4,-6,-9,-11,-13,-14,-15,-17,-21,-22 CDC CHR Antonelli et al (19) that "an error and disregulation" in the embryonal Anlage may lead to development of tumours (17). Wilms' tumour (WT) and papillary RCT have already been recognized as a useful model to explore the tumour development from "not differentiated superabundant" embryonal rest cells (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Now, we add MTSCC to this group of tumours. WT, MTSCC and papillary RCT display morphological variations corresponding to impaired differentiation of blastemal cells, albeit at different time of mesenchyme to epithelium transition affecting different cell lineages (19). The embryonal origin of MTSCC may explain its morphological variations making the diagnosis uncertain in some cases.…”
Section: Discussionmentioning
confidence: 99%